Impact of the Adoption of Photovoltaic System on Households’ Energy Consumption: The Evidence from the Urban Area in Jaffna District in Northern Sri Lanka - Sooriyakumar, Krishnapillai; Hariskar, Raveendran; Sarujan, Sathiyamoorthy; Sivashankar, Sivakumar (International Journal of Energy Economics and Policy, 2025)
Photovoltaic system (PV) is a classic example of renewable energy sources and a potential alternative for fossil fuels to satisfy the energy needs of households and industries. However, the adoption of PV at the household level remains very low, especially in the developing countries. This study investigates the effect of the adoption of PV on the electricity usage of urban households in Jaffna district in northern Sri Lanka using the primary data collected from the sample of 303 households including both the adopters and non-adopters of PV who were randomly selected from urban population. To account for selection bias, this study employs propensity score matching method and estimate the impact of adopting PV on households’ energy consumption. The outcome of average treatment effect and average treatment effect on the treated prove that the adoption of PV has a significant positive effect on household’s energy consumption, coefficients with a value of 45.743 (P < 0.01) and 29.372 (P < 0.1) respectively. The results clearly show the adoption of PV at the household level significantly and positively increases household’s total electricity consumption, suggesting the significance of promoting renewable energy sources as a potential way to tackle the issues of climate change and ensure clean development.